Susungan: Tradisi Adat Maanta Mayit Ka Pandan Kuburan - Adam Pramugio Putra; Fira Permata Putri; Iman Ashar Tanjung; M Rifki Haikal; Risky Amalia (Ethnography : Journal of Cultural Anthropology, 2025)
Nagari Bukik Tandang, located in Bukik Sundi District, Solok Regency, West Sumatra, has a rich history and traditions deeply rooted in Minangkabau customs. Established by early settlers around 1680, the community of Nagari Bukik Tandang formed with five major clans inhabiting the area. One of the unique traditional customs in this Nagari is "Susungan," a burial procession using a traditional bamboo bier, symbolizing the spirit of mutual cooperation and togetherness in the community. This tradition encompasses the entire burial process, from the preparation of the body to its final journey to the resting place in the cemetery. The components of the Susungan, such as the "janjang" (base), "tunggak nan ampek" (four pillars), and "puncak talang" (top canopy), hold deep symbolic meanings, reflecting the role of customs and the value of unity within the society. Although this tradition has been passed down orally without written records, the Susungan ritual remains well-preserved as an important cultural heritage in Nagari Bukik Tandang, embodying solidarity and respect for the deceased. Keyword: Susungan, Death Rituals, Minangkabau